Legitimacy in international society - Ian Clark (Oxford University Press, 2005)
Policy makers and publics alike regularly debate the legitimacy of international events, such as the war on terror, or war in Iraq. But what exactly does legitimacy mean in an international setting? This major new work provides the first historically and theoretically grounded analysis of this critical issue in contemporary society. Drawing on both historical and recent events, Clark provides a lucid demonstration of how legitimacy is a highly political condition, related in complex ways to consensus, other values, and balances of power